Great Pianists on Piano Playing. Godowsky, Hofmann, Lhévinne, Paderewski and 24 Other Legendary Performers - Cooke, James Francis (Mineola Dover, 1999)
Great pianists discuss topics ranging from piano technique and musical development to becoming a virtuoso. Included are Busoni's "Important Details in Piano Study," Rachmaninoff's "Essentials of Artistic Playing," Paderewski's "Breadth in Musical Art," and much more. Includes 2 introductory essays, artist biographies, artists' study questions, more.
Keywords: Piano; Biography; Music history